TRANSHUMANISM IN RUSSIA: SOCIAL ACTIVIVITIES - Olga V. Polyakova (Высшее образование в России, 2016)
Owing to the achievements of biotechnological revolution in the second half of the XX century which open the way to unlimited human enhancement, a new view on life, transhumanism, has emerged. The followers ofthe new ideology stand for the further evolution of Homo sapiens with the aid of new technologies. Immortality is declared to be the ultimate objective of their activity. However the aim may seem fantastic, the new ideology has a lot of followers all over the world including Russia. Within the framework of this article the author makes an attempt to analyze transhumanist social activities and to identify the real, but not declared, purpose of their practices. The author draws a parallel between transhumanist organizations and totalitarian sects and pseudo-scientific societies. Transhumanist can also be viewed as self PR and a phenomenon of social mimicry.